Human resources' student's sensitivity to factors of sustainability - Pestana, M. H.; Parreira, A. M. (Ensaio: Avaliação e Políticas Públicas em Educação, 2016)
This paper analyzes the sensitivity of college students to sustainability factors, including their definition of the concept and their perception of human resources management as a factor of sustainability. The prospects of the construct of sustainability – from the United Nations Conference in 1972, in Stockholm, to contemporary achievements and theoretical explorations-are reviewed as a conceptual framework. The research among college students has been developed along two lines: the study of their idea of sustainability; and the assessment of people’s management practices as a factor of sustainability. The research combined the use of a semantic differential questionnaire and a focus group to collect data and to complement the quantitative data with a more qualitative vision and understanding. The results consolidate the idea that: it is interesting to use the sustainability concept in combination with the complexity level of contexts; students of HRM are well informed about the concept; and that their attitudes on the subject are positive, as they are motivated to lead companies to adopt sustainable practices in human resource management, as an effective sustainability factor.